Analysis of the Operating Costs of Passenger Cars Declared by Vehicles’ Manufacturers and Obtained by Users - Piotr Gorzelańczyk; Bartlomiej Kelm (Communications - Scientific letters of the University of Zilina, 2022)
Every year, there are more and more cars on the roads that cause pollution. To reduce it, conventional vehicles have started to be replaced by electric and hybrid vehicles. Therefore, the average fuel/energy consumption of electric, hybrid, spark ignition and self-ignition vehicles over a test distance of 100 km was investigated. The test results were then compared to the manufacturer’s data and the average difference between the manufacturer’s data and the test data is shown. The largest average difference in fuel consumption between the manufacturer’s data and the test data was observed for hybrid vehicles (over 230 %) and the smallest for electric vehicles (less than 10 %) and spark ignition vehicles (almost 18 %). Considering costs, the largest difference between manufacturer’s data and test data is observed, as in the previous case, in electric vehicles (0.25 €) and the largest in hybrid vehicles (almost 6 € per 100 kilometers driven).